2017
DOI: 10.1093/mnras/stx2725
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for distributed gas sources of hydrogen halides in the coma of comet 67P/Churyumov–Gerasimenko

Abstract: Rosetta has detected the presence of the hydrogen halides HF, HCl, and HBr in the coma of comet 67P/Churyumov-Gerasimenko. These species are known to freeze out on icy grains in molecular clouds. Analysis of the abundances of HF and HCl as a function of cometocentric distance suggests that these hydrogen halides are released both from the nucleus surface and off dust particles in the inner coma. We present three lines of evidence. First, the abundances of HF and HCl relative to the overall neutral gas in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 69 publications
1
12
0
Order By: Relevance
“…This trend is observed with increasing elevation, which would then imply that evaporation of some dark material took place in the inner coma. Evidence for the degradation of grains in the coma of 67P are however still very sparse (e.g., hydrogen halides and glycine are released from dust, De Keyser et al 2017;Altwegg et al 2016). Incidentally, we note that, in presence of rapidly subliming (i.e., small and dirty) ice grains, the trend would have been opposite.…”
Section: Radial Variation Of the Bolometric Albedomentioning
confidence: 65%
“…This trend is observed with increasing elevation, which would then imply that evaporation of some dark material took place in the inner coma. Evidence for the degradation of grains in the coma of 67P are however still very sparse (e.g., hydrogen halides and glycine are released from dust, De Keyser et al 2017;Altwegg et al 2016). Incidentally, we note that, in presence of rapidly subliming (i.e., small and dirty) ice grains, the trend would have been opposite.…”
Section: Radial Variation Of the Bolometric Albedomentioning
confidence: 65%
“…No such distributed source detection has been reported so far, however. It is interesting to note that De Keyser et al (2017) have also reported a distributed source for HCl and HF due to waterice sublimation from dust particles in the atmosphere of comet 67P. No distributed source of water is detected in their data either, however, because the contribution of sublimating water from the icy dust particles to the total water budget in the coma is suspected to be minor.…”
Section: Discussionmentioning
confidence: 96%
“…The escaping material may still contain volatiles which affect the dust-to-gas ratio, see e.g. De Keyser et al (2017) and Altwegg et al (2016). In addition, the dust-to-gas ratio may differ from the dust-to- 4.8 ± 1.5 × 10 9 2.0 6.1 ± 0.3 × 10 2 CO 2 9.5 ± 3.8 × 10 33 7.0 ± 2.8 × 10 8 4.9 8.6 ± 0.4 × 10 CO 3.6 ± 1.1 × 10 33 1.7 ± 0.5 × 10 8 1.7 2.0 ± 0.1 × 10 O 2 2.6 ± 0.8 × 10 33 1.4 ± 0.4 × 10 8 1.8 1.4 ± 0.7 × 10 Table 1.…”
Section: Global Gas Productionmentioning
confidence: 99%